Exploring the Meanings of the Figurative Language in A Dog’s Way Home Movie - Pradita, Dara; Adi, A B Prabowo Kusumo; Suwarti, Tarcisia Sri (English Education Department, 2025)
This research investigates how figurative language expresses deeper meanings and emotional dimensions in the film. While figurative language is widely used in cinematic works, studies that explore its types, implied meanings, and narrative contributions are still limited. Therefore, this study aims to analyze the types and meanings of figurative language found in A Dog’s Way Home, using M.H. Abrams’s classification of figurative language and Geoffrey Leech’s theory of meaning. A qualitative descriptive method was employed to analyze selected dialogues and scenes that contained figurative expressions. A total of 64 figurative expressions were identified, with personification (21.9%) and irony (20.3%) as the most frequent types, followed by simile, metaphor, hyperbole, metonymy, paradox, and synecdoche. Each expression was examined to reveal conceptual, connotative, affective, and social meanings. The findings show that figurative language in the film not only serves stylistic functions but also deepens the thematic and emotional aspects of the story. It conveys themes of loyalty, loneliness, resilience, and the strong bond between humans and animals, especially through the portrayal of the protagonist’s internal struggles. This study contributes to the field of film and language studies by highlighting the significant role of figurative language in enriching narrative depth. The implication suggests that figurative language analysis can be a useful approach in educational contexts to foster deeper interpretation of film texts